Development of international trade in intellectual property items - Radjabov Bunyod Abdukhalilovich (Universitas Muhammadiyah Sidoarjo, 2019)
The article is based on the growing role of international trade in innovation and intellectual property in the global economy. The trends of international trade in intellectual property and the experience of developed countries are explored. Proposals and recommendations on participation in the international market of intellectual property have been developed as a target of the innovative development of Uzbekistan.